Copper loss analysis and loss separation method in a dynamic process of ultra‐high speed motor with slotless stator. Issue 4 (23rd December 2022) - Gao, Qixing; Wang, Xiaolin; Gu, Cong; Zhang, Yan
Abstract: Different from the copper loss of general permanent magnet (PM) motors, the copper loss of ultra‐high‐speed permanent magnet motors (UHSPMSM) includes DC losses and eddy current losses, which lead to difficulty in analysis. In consideration of the influence of speed, wire diameter and current harmonic loss, DC copper loss and eddy current copper loss are calculated and analysed, respectively, so as to find the main excitation source of copper loss of UHSPMSM. Then, in order to calculate the Litz wire loss in a slotless stator, a Litz wire loss equivalent model is established, which can be used to accurately and quickly calculate the DC loss and eddy current loss of Litz wire independently. Finally, a copper loss separation method is designed to test copper loss of 550, 000 rpm UHSPMSM considering the influence of the rotor PM flux at ultra‐high speed. The theoretical analysis and experimental results verify each other. In the end, the experimental results verify the effectiveness of theoretical analysis. Abstract : In consideration of the influence of speed, wire diameter and current harmonic loss, DC copper loss and eddy current copper loss are calculated and analysed, respectively, so as to find the main excitation source of copper loss of ultra‐high‐speed permanent magnet motors (UHSPMSM). In order to calculate the Litz wire loss in a slotless stator, a Litz wire loss equivalent model is established, which can be used to accurately and quickly calculate the DC loss and eddy current loss of Litz wire independently.